Hubungan School Climate Dengan Student Well Being Pada Siswa Sekolah Menengah Pertama - Sari, Elen Nofita; Fitriani, Yulia; Pertiwi, Yuarini Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the relationship that occurs, whether there is a relationship or not between the variables of School Climate (X) with Student Well Being (Y). The method used for data collection in this study is in the form of filling out a questionnaire or questionnaire with a quantitative approach. This study uses the Slovin formula for the sampling method with the results of 100 respondents who are students of MTS X in Bekasi City. In this study, data analysis was carried out using normality tests and correlation tests. Based on the results of the study conducted which discusses the relationship between student well being and school climate in students at MTs Nurul Anwar, it can be concluded that the alternative hypothesis (Ha) is proven which means Ha is accepted which has the result that there is indeed a significant relationship between the variables of student well being and school climate. This study has a positive relationship where the school climate is high then the student well being owned is also high in MTs Nurul Anwar students, and vice versa if the school climate is low then the student well being owned by students at MTs Nurul Anwar will also be low. The results of the categorization test on the student well-being variable at Mts Nurul Anwar fall into the moderate category. This finding indicates that despite a positive relationship between school climate and student well-being, the overall well-being of Mts Nurul Anwar students has not yet reached an optimal level. The results of the school climate categorization test indicate that the majority of students at Mts Nurul Anwar fall into the high category, meaning that they have excellent physical and non-physical safety, teacher-student relationships, and peer relationships.